2019
DOI: 10.1074/jbc.ra118.006393
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of erythrocyte Na+/K+/2Cl− cotransport by an oxygen-switched kinase cascade

Abstract: Edited by Mike ShipstonMany erythrocyte processes and pathways, including glycolysis, the pentose phosphate pathway (PPP), KCl cotransport, ATP release, Na ؉ /K ؉ -ATPase activity, ankyrin-band 3 interactions, and nitric oxide (NO) release, are regulated by changes in O 2 pressure that occur as a red blood cell (RBC) transits between the lungs and tissues. The O 2 dependence of glycolysis, PPP, and ankyrin-band 3 interactions (affecting RBC rheology) are controlled by O 2 -dependent competition between deoxyhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 79 publications
0
18
0
1
Order By: Relevance
“…; Zheng et al. ), who propose that enhanced binding of deoxygenated Hb to band 3 displaces glycolytic and other enzymes, notably WNK1, leading to inhibition of the transporter. In sickle cells, as O 2 levels are reduced, the activity of KCC goes through a nadir at about half saturation of Hb for O 2 (Gibson et al.…”
Section: Discussionmentioning
confidence: 99%
“…; Zheng et al. ), who propose that enhanced binding of deoxygenated Hb to band 3 displaces glycolytic and other enzymes, notably WNK1, leading to inhibition of the transporter. In sickle cells, as O 2 levels are reduced, the activity of KCC goes through a nadir at about half saturation of Hb for O 2 (Gibson et al.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of red cell NKCC, WNK1 appears to be responsible for increased activity following deoxygenation [63]. KCC activity is also oxygen dependent, although in a reciprocal fashion being activated by oxygenation rather than deoxygenation.…”
Section: Resultsmentioning
confidence: 99%
“…Knockout studies in mice have indicated a role for the Src and Syk tyrosine kinases [13, 41, 42], with the conjugate phosphatases identified as PP1, PP2A, or PP2B [2, 3]. More recent publications provide molecular evidence for a role for WNK1 and possibly the functionally redundant WNK substrates SPAK/OSR1 in inhibition of KCC and stimulation of coordinate cotransport, NKCC, in red cells [15, 50, 63]. This paper provides the first demonstration of a functional role for WNKs in control of KCl cotransport in red cells from patients with sickle cell anaemia (SCA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synchronous decrease in sodium and potassium concentration in erythrocytes and muscles of roaches and breams at the initial period of hyponatremia indicates that the possible mechanism of their excretion from cells may be connected to the activation of Na + -K + -2Clcotransporter. This carrier is found on the membranes of various types of cells, including those of epithelium, endothelium, nerves, muscles, fi broblasts, and red blood cells (58)(59)(60)(61)(62). The participation of the Na +-K +-2Clcotransporter in the regulation of cellular volume has been studied in vitro.…”
Section: Protective Mechanisms Opposing Hyponatremia In Vivo In Erythmentioning
confidence: 99%